Short-term bridging and bird-dog exercise programs did not enhance trunk performance and whole-body dynamic balance in young physically active males: A double-blind randomized trial - Amaya Prat-Luri; Francisco J. Vera-Garcia; Pedro Moreno-Navarro; Casto Juan-Recio; Javier de los Ríos-Calonge; Juan R. Heredia-Elvar; Jose L. L. Elvira; David Barbado (PLoS ONE, 2025)
Bridges and bird-dog exercises are commonly used in general training, as well as in warm-up and cool-down routines for young athletes to boost performance and prevent injuries. They are frequently paired with limb and other trunk exercises, and performed without precise control over intensity, which hinders the understanding of their actual impact. This double-blinded randomized controlled trial aimed to evaluate the effects of two bridging and bird-dog exercise programs (one emphasizing intensity, the other volume) on trunk performance and whole-body balance. Sixty participants were randomly assigned to a control group and two experimental groups, both of which performed bridging and bird-dog exercises at a specific intensity controlled by a smartphone-accelerometer. The exercises were conducted twice a week for six weeks at the university sports complex. The effects were assessed on: (i) trunk stability, through the bridging and the bird-dog lumbopelvic postural control, the unstable sitting and the sudden loading sitting tests, (ii) trunk endurance, through the front and the dominant side bridge endurance, and the Biering-Sorensen tests, and (iii) whole-body dynamic balance, through the Y-Balance, the tandem and single-leg stance, and the single-leg triple hop tests. Pre-post changes were reported in both absolute (Δ) and relative (Δ%) values. A two-way mixed ANOVA assessed differences between experimental and control groups, while paired t-tests analyzed within-group pre-post changes with a significance level set at p < 0.05. Neither of the experimental groups showed improvements in trunk performance and balance compared to the control group or among themselves. Nonetheless, the higher intensity group elicited greater pre-post changes in the bridging and the bird-dog lumbopelvic postural control tests (−10.4 ≤Δ% ≤−16.9 vs −4.8 ≤Δ% ≤−13.6), whilst the higher volume group did in the trunk endurance tests (10.9 ≤Δ% ≤19.5 vs 7.1 ≤Δ% ≤15.5). The lack of significant between-group differences may be due to the low exercise doses, typical for these exercises in fitness and rehabilitation routines, and the participants being active young males with no apparent postural control deficits. Additionally, the pre-post changes in the experimental groups highlight the specificity of exercise adaptations. This study questions the effectiveness of bridging and bird-dog exercises for improving trunk performance and whole-body balance in this population, beyond the tasks used in training.